GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 56 species occurrences available in GBIF matching the query: TaxonKey: Morchella conica Pers., 1818 Country: Mexico Geometry: POLYGON((-150.82 -89.14,-150.82 89.14,10.90 89.14,10.90 -89.14,-150.82 -89.14)) HasGeospatialIssue: false. The dataset includes 56 records from 2 constituent datasets: 2 records from Hongos del estado de Veracruz. 54 records from Distribución conocida y potencial de 48 especies de hongos silvestres comestibles en la región central del país. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences